1991
DOI: 10.1051/jp4:19913116
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Equations for Annealed and Explosively Shocked Iron for Application to High Strain Rates and Large Strains

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…For both shocked and unshocked materials the work hardening rate is independent of the strain rate [3]. This characteristic is a basic assumption of the constitutive equation proposed by Armstrong and Zerilli for body centred cubic metals at small strains, and fuelled the development of equation 4 for the flow stress,σ.…”
Section: Goldthorpe Modified-armstrong-zerilli Body Centred Cubic Conmentioning
confidence: 97%
See 4 more Smart Citations
“…For both shocked and unshocked materials the work hardening rate is independent of the strain rate [3]. This characteristic is a basic assumption of the constitutive equation proposed by Armstrong and Zerilli for body centred cubic metals at small strains, and fuelled the development of equation 4 for the flow stress,σ.…”
Section: Goldthorpe Modified-armstrong-zerilli Body Centred Cubic Conmentioning
confidence: 97%
“…After comparing work hardening curves at different temperatures Goldthorpe found a small but steady divergence with increasing strain [3]. Further investigation then identified that as the temperature of a shocked material diverges from ambient it increasingly diverges from the unshocked data.…”
Section: Goldthorpe Modified-armstrong-zerilli Body Centred Cubic Conmentioning
confidence: 97%
See 3 more Smart Citations